Simple waves with finite amplitude in axially-symmetrical channels with annular cross-section - T. ZAMORSKI (Archives of Acoustics)
Propagation of a plane progressive sound wave with finite amplitude in a waveguide with variable annular cross-section was considered. It was assumed that this waveguide was filled with loss less gaseous medium and the wave with finite amplitude was generated by a annular piston, which vibrated in harmonic motion at the inlet of the waveguide. The considerations were done in Lagrangian coordinates.